A Comparative Study to Analyze the Perspectives, Interests, and Barriers Towards Research Project Among Undergraduate Students in The Universities of Faisalabad - Muhammad Shoaib; Anam Fatima; Kaiynat Shafique; Zamin Abbas Syed; Hafiz Muhammad Almas Sabir; Iqra Tahir; Urooj Manzoor (International Health Review, 2023)
Research plays a vital role in evaluating a nation's scientific progress, especially in the field of medical science. The purpose of the study was to analyze and compare the perspectives, interests, and barriers encountered by undergraduate students in Physical Therapy and Human Nutrition and Dietetics concerning research. It was a cross-sectional study. Study settings included GCUF, UAF and TUF. The study was conducted from September 2019 to February 2020. 148 participants were recruited according to the defined selection criteria. Employing a simple random sampling methodology, data was gathered exclusively from final-year undergraduate students pursuing DPT and HND, using a modified questionnaire. From 148 students (66 HND, 82 DPT), 38.5% of participants acknowledged the constructive and beneficial nature of research. Additionally, 36.49% strongly expressed their desire to delve into the intricacies of research. The Chi-square test demonstrated no statistically significant differences in perspectives, interests, and barriers toward research projects between HND and DPT students (p>0.05). The students' perspectives and interests in research were predominantly positive, reflecting their enthusiasm and curiosity. However, they also faced notable barriers and challenges including inadequate time and monetary support, insufficient training for research, and lack of supervision that hindered their engagement in research projects.